IDENTIFICATION OF STUDENTS' PHYSICS LEARNING UNDERSTANDING WITH FOUR-TIER DIAGNOSTIC TEST ON EQUILIBRIUM OF RIGID BODY TOPIC - Marpaung, Novia Dwi Kristiani ((IPER) Indonesian Physics Education Research, 2024)
This research aims to determine students' understanding of the equilibrium of rigid body topic by four-tier diagnostic test. This research was conducted in one of the schools in North Sumatra for students in class XI IPA in the 2023/2024 school year, totaling 53 students. Sampling was done by simple random sampling method. Data collection techniques include tests, interviews, and questionnaires. The test instrument used was a valid four-tier diagnostic test with a test reliability value of 0.719 which amounted to 20 items from 14 question indicators. Student results are categorized as student understanding which is divided into Scientific Conception (10%), Rarely Misconception (17%) caused by students being wrong in determining the reason, Negative False (14%) caused by students who are wrong in answering the question but correct in giving reasons, Lack of Knowledge (31%) caused by students who were unsure of the answer they chose, and Misconception (28%) due to students' ability to solve calculation-based problems and image analysis but have confidence in their answers on the topic of Equilibrium of Rigid Bodies.